Numerical study on thermal-induced lubricant depletion in laser heat-assisted magnetic recording systems - Zeng, Yan (2013)
This paper presents a numerical investigation of heat transfer and lubricant depletion on the hard disk in a heat-assisted magnetic recording (HAMR) system. The heat is induced by a laser pulse shooting down from a slider flying over the disk coated with a thin layer of lubricant. The main mechanisms to cause the lubricant depletion are examined by taking into account of effects associated with evaporation enthalpy, thermal induced surface tension and initial lubricant film thickness. The results show that the evaporation has a dominant effect at a lower evaporation enthalpy, while the thermocapillarity plays a main role at a higher evaporation enthalpy. The lubricant depletion is also found to be affected by the initial thickness of the lubricant film, mainly through the influence on the evaporation rather than on the thermocapillarity. In addition, the effect of lubricant accommodation coefficient on the evaporation has been addressed for the first time in the present study. It is found that a full accommodation assumption adopted in previous numerical studies may overestimate the actual evaporation rate, and a suitable value for the accommodation coefficient between 0 and 1 is required in the prediction in order to yield a good agreement between the simulation results and the experimental data.